2014
DOI: 10.1249/mss.0b013e31829f83a0
|View full text |Cite
|
Sign up to set email alerts
|

Sporadic and Bouted Physical Activity and the Metabolic Syndrome in Adults

Abstract: Within this representative sample of Canadian adults, sporadic MVPA was associated with the MetS to a similar order of magnitude as an equivalent volume of bouted MVPA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
71
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 22 publications
2
71
0
3
Order By: Relevance
“…Even though the current physical activity guidelines recommend that activity be accumulated in bouts of ≥10 minutes, most of these studies also examined the relative benefits of sporadic MVPA. The few studies specifically examining the value of bouted physical activity showed that sporadic versus bouted activity had similar associations with the metabolic syndrome, waist circumference, and body mass index . However, all of these studies employed cross‐sectional designs and examined intermediate end points.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the current physical activity guidelines recommend that activity be accumulated in bouts of ≥10 minutes, most of these studies also examined the relative benefits of sporadic MVPA. The few studies specifically examining the value of bouted physical activity showed that sporadic versus bouted activity had similar associations with the metabolic syndrome, waist circumference, and body mass index . However, all of these studies employed cross‐sectional designs and examined intermediate end points.…”
Section: Discussionmentioning
confidence: 99%
“…Healy et al, showed associations between bouts of accelerometer measured sedentary time >30 minutes and obesity (19), and Carson et al, showed bouts of 20 minutes of sedentary time were associated with cardiometabolic biomarkers (5). Research has also begun to differentiate the relative benefits of sporadic-MVPA and MVPA-guideline in relation to cardiovascular health and metabolic syndrome (10). The present findings provide reassurance that the metrics used in these studies are reproducible and predictive of behavioral patterns.…”
Section: Discussionmentioning
confidence: 99%
“…First, we employed a prospective study design, which is an advance over previous cross-sectional studies. (4, 10, 21) Second, we analyzed data from a large, well characterized cohort with standardized measures of CVD risk factors in middle aged adults with close to equal proportions people who are White and Black. Lastly, we were able to examine short spurts of MVPA from a well-validated and objective measure of physical activity, the ActiGraph monitor.…”
Section: Discussionmentioning
confidence: 99%
“…However, short spurts may still be associated with health benefits. Recent cross-sectional studies objectively measuring physical activity with monitors show that short spurts of MVPA have a similar protective association with the prevalence of cardiovascular disease risk factors,(10) markers of obesity,(21) and metabolic syndrome(4) as bouted MVPA, i.e., MVPA lasting ≥ 10 minutes. However, the cross-sectional design of these studies limits the ability to establish a causal association.…”
Section: Introductionmentioning
confidence: 99%